Antigen- and receptor-driven regulatory mechanisms. II. Induction of suppressor T cells with idiotype-coupled syngeneic spleen cells (The Rockefeller University Press, 1979)
Anti-p-azobenzenearsonate (ABA) antibodies, coupled covalently to normal syngeneic spleen cells and then given intravenously to normal animals, were found to be potent tolerogens for delayed-type hypersensitivity (DTH) to ABA. The ability of the antibody-coupled cells to induce tolerance was determined to be a result of the cross- reactive idiotype (CRI+) fraction of the antibodies, because anti-ABA antibodies lacking the CRI+ components when coupled to spleen cells were unable to cause any significant inhibition. Furthermore, genetic analysis revealed that the ability of CRI-coupled cells to inhibit ABA- specific DTH is linked to Igh-1 heavy chain allotype, in as much animals which possess heavy chain allotypes similar to that of A/J were sensitive to this inhibition. Adoptive transfer experiments provided evidence that CRI-coupled cells induce suppressor cells, and spleen cells or thymocytes from animals received CRI-coupled cells were able to transfer suppression to naive recipients. In addition, treatment with anti-Thy1.2 serum plus complement completely abrogated their ability to transfer suppression. Thus, this active suppression is a T- cell-dependent phenomenon. In investigating the specificity of these suppressor T cells, it was found that they functioned in an antigen- specific manner and were unable to suppress the development of DTH to an unrelated hapten 2,4-dinitro-1-fluorobenzene.